Long-Term Clinical and Radiological Results After Hook Plate Osteosynthesis of Lateral Clavicle Fractures. Issue 7 (July 2021) - Baunach, Daniel; Eid, Karim; Ricks, Matthew; Borbas, Paul
Abstract : Objectives: To assess both clinical and radiological long-term outcomes after hook plate osteosynthesis for Neer type II lateral clavicle fractures. Design: Retrospective case series. Setting: Level-1 trauma center. Patients/Participants: Patients who underwent open reduction internal fixation with a hook plate for displaced fractures of the lateral third of the clavicle (Neer type II) at a single trauma hospital were identified. Intervention: Lateral clavicle open reduction internal fixation with a hook plate. Main Outcome Measures: At the first of 2 long-term follow-up appointments, bilateral magnetic resonance imaging (MRI) scans and strength measurements were performed, Constant–Murley score, subjective shoulder value (SSV), and Oxford shoulder score (OSS) of both shoulders were obtained. At the second follow-up, specific acromioclavicular (AC) score, SSV, and OSS were obtained. Results: Twenty-one patients (mean age, 29.5 ± 9.7 years) could be included who were available for at least 1 of 2 follow-ups after 7.4 years (±2.3) and 13.9 years (±2.2). Bony union was achieved in all patients (100%) at an average of 3.4 months (±1.4). The hook plate was removed at an average of 5.5 months (±3.3) after initial surgery in all patients. No significant side-to-side differences were found in OSS, Constant–Murley score, SSV, and specific AC score and for strength testing and MRI scans. Conclusions: Long-term outcome after hook plate fixation of Neer type II lateral clavicle fractures demonstrated good clinical results and shoulder strength without higher radiographic rates of AC joint osteoarthritis, subacromial impingement, or rotator cuff lesions. That may be related to a standardized early plate removal after bony fracture union. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.